Evaluation of Technology-Based Learning on Effectiveness and Student Satisfaction: a Case Study at the Tax Center UNPAD - Retta Farah Pramesti; Agus Puji Priyono; Rosyani Muthya; Aulia Baharudin (Journal of Vocational Education Studies, 2026)
This study aims to evaluates the effectiveness and satisfaction of technology-based instruction that combines Blended Learning and Student-Centered Learning (SCL) in Income Tax courses at the Tax Center, Universitas Padjadjaran (UNPAD). Using a mixed-methods design, survey data from 52 students were analyzed with multiple regression to test the effects of student involvement, student roles, and implementation challenges on learning effectiveness and satisfaction; interviews and document analysis enriched the interpretation. Quantitative results show that both student involvement and student roles are positively associated with learning effectiveness, whereas implementation challenges do not exert a meaningful impact on effectiveness in this context. In contrast, student satisfaction is shaped by all three factors, with challenges emerging as the strongest driver, indicating that even highly engaged, well-positioned learners may report lower satisfaction when facing technical or organizational barriers. Qualitative findings corroborate these patterns: students value flexibility, interactivity, and the ability to review recordings, yet cite connectivity issues, reduced hands-on practice, and concentration lapses during long online sessions. Students propose practical remedies such as on-camera policies, contingency plans for disruptions, and recording face-to-face sessions for later review. The study highlights the need to pair active, role-rich pedagogy with robust facilitation and infrastructure to sustain both effectiveness and satisfaction in vocational tax education.